Religious Understanding as a Predictor of Adolescent Religious Behavior: An Empirical Study in Central Lampung, Indonesia - Ria Dona Sari; Mukhtar Hadi; Buyung Syukron (2 issues per year (June and December), 2025)
Purpose: This study investigates the extent to which religious understanding predicts the religious behavior of adolescents in Central Lampung, Indonesia. In many developing societies, religious education plays a central role in shaping moral orientation and behavioral patterns among youth. However, limited empirical research has examined this relationship quantitatively. This study seeks to fill that gap by exploring how variations in adolescents’ comprehension of Islamic teachings influence their practical expressions of faith in daily life. Method: A quantitative correlational design was employed, involving 27 adolescent respondents selected from a population of 142 in Ngestirahayu Village, Punggur District. Data were collected through questionnaires, interviews, and documentation techniques. The analysis used the Chi-Square (χ²) statistical test to determine the strength and significance of the relationship between religious understanding and religious behavior. Findings: The results revealed a significant correlation between religious understanding and religious behavior (χ² = 30.59; p < 0.05), with a correlation coefficient of 0.7 indicating a moderate yet positive relationship. Adolescents with a higher level of comprehension of religious principles demonstrated more consistent worship practices, moral conduct, and social responsibility. Significance: The study highlights the predictive role of religious understanding in shaping adolescents’ spiritual and ethical development. Its findings underscore the importance of integrating cognitive, affective, and behavioral components of religious education into youth programs. Strengthening religious literacy at the community level can foster more grounded moral awareness and contribute to social harmony within multicultural contexts.